Let $S$ be a non empty subset of $\mathbb{R}$ having supremum and $T=\{x\in\mathbb{R}: x-a \in S\}$, then $\forall a \in \mathbb{R}$ , $\sup T=a+\sup S$.

My proof:- Let $x\in T$

$\implies x-a≤ \sup S$

$\implies x≤ \sup S+a$

$\because \sup T $ act as an least upper bound of $T $

$\therefore \sup T≤a+\sup S$

How to prove the converse? Please help me.


We have that if $y \in S$ then $(y+a)-a \in S$

Thus $$(y+a) \in T \Rightarrow y+a=t \in T \Rightarrow y=t-a \leqslant \sup T -a$$

So $\sup S \leqslant \sup T-a \Rightarrow \sup S+a \leqslant \sup T$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.